Hakekat Agama Dalam Perspektif Filsafat Perenial - Amallia, Siti (Universitas Islam Negeri Raden Intan Lampung, 2019)
Religion in life aside from functioning as a guide to life individually, religion also functions as an instrument in dealing with all differences. But now, religion in empirical reality begins to lose its social function. religious guidance that teaches to live peacefully and love one another, turns into a disaster that hates and destroys each other. Therefore, the discussion that will be examined in this article is: How does perennial philosophy explain the nature of religion? This problem will be examined by researchers with a descriptive approach, hermeneutics, and historical continuity. The nature of religion in the perspective of perennial philosophy can be seen from two sides, namely exoteric and esoteric. The exoteric side sees the nature of religion in terms of forms related to historicity, culture, customs, and ethnicity in certain societies. While the esoteric side sees the nature of religion by finding common ground to trace the historical chain of the growth of religion. The meeting point is located at the level of substance that has a transcendent unity. So, from an esoteric point of view the nature of religion is one not divided, but from this one radiates various truths. When the nature of religion is seen in different forms, then it is of relative value, because each adherent of the religion has an exclusive claim about the religion that is adhered to. But when religion is seen in transcendent unity, that is called absolute truth.